Acute pulmonary embolism – how to diagnose, treat and prevent recurrent episodes? - Budaj, Anna M. (Przewodnik Lekarza/Guide for GPs, 2007)
Pulmonary embolism, along with deep vein thrombosis, is a clinical manifestation of venous thromboembolism, which can be experienced both in hospital wards and in outpatient clinics. The diagnostic process depends on pulmonary embolism probability assessment. Pharmacological management depends on severity of the disease. It is necessary to increase physicians’ awareness of the problem and watchfulness, while establishing diagnosis in patients whose symptoms may be due to venous thromboembolism. The aim of this review is to present recommended diagnostic and pharmacological management in pulmonary embolism based on current guidelines and selected medical publications.